VALUES EDUCATION ACCORDING TO YUSUF QARDHAWY AND KI HAJAR DEWANTARA - Purwanto Purwanto; Muhammad Ulfi FAdli; Wildan Nur Hidayat (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2023)
Until now, education is the shaping human character hope for the better. Therefore, education needs to be developed to produce reliable generations through the Yusuf Qrdhawy and Ki Hajar Dewantara though as good figure. This research is a library research where researchers used several references such as journals, books and others to collect and use as research references. The result of the research is that Yusuf Qardhawi says that education is the whole man education, his mind and heart, spirit and body. While Ki Hadjar Dewantara wants that all of teaching and learning, the teachers must integrate the materials of all subjects with ethical education.